2020
DOI: 10.1186/s12889-020-09139-w
|View full text |Cite
|
Sign up to set email alerts
|

Work-life balance and self-reported health among working adults in Europe: a gender and welfare state regime comparative analysis

Abstract: Background: The pressing demands of work over the years have had a significant constraint on the family and social life of working adults. Moreover, failure to achieve a 'balance' between these domains of life may have an adverse effect on their health. This study investigated the relationship between work-life conflict and self-reported health among working adults in contemporary welfare countries in Europe. Methods: Data from the 6th European Working Conditions Survey 2015 on 32,275 working adults from 30 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 88 publications
2
32
0
1
Order By: Relevance
“…[ 8 ] Recent research shows that there is a strong connection between WLI and poor self-reported health among adult workers. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Recent research shows that there is a strong connection between WLI and poor self-reported health among adult workers. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences in social status have existed for a long time (Ciabattari, 2001 ; Mensah and Adjei, 2020 ; Takahashi et al, 2020 ). In primitive society, due to the difference in body shape and strength between men and women, men were better able to undertake the power-type labor.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the pandemic, achieving work-life balance has grown increasingly complex due to digital integration and remote working scenarios, resulting in an "always on" culture that blurs the line between work and personal life. This phenomenon has inspired several researchers to conduct work-life balance studies (Mensah & Adjei 2020;Nwagbara 2020;Pattusamy & Jacob 2017;Ramachandran, 2020;Wolor, Kurnianti, Zahra & Martono, 2020). This digital integration also has contributed to the development of a more inclusive model of WLB.…”
Section: Introductionmentioning
confidence: 99%
“…The sudden implementation of WFH has contributed to many problems. Many researches were done to study the difficulties or problems arising from this new WFH practice (Mensah & Adjei, 2020;Pirzadeh & Lingard, 2021;Ramachandran, 2020). This unexpected widespread adoption of home-based teleworking was unprecedented.…”
Section: Introductionmentioning
confidence: 99%